PENGENALAN APLIKASI UKM DAN CARA PENGGUNAANNYA BAGI UKM DI WILAYAH KELURAHAN BUGANGAN SEMARANG - Rinawati, Tri; Niati, Asih; Ariefiantoro, Teguh (POLITEKNIK LP3I JAKARTA, 2023)
MSMEs in the Bugangan sub-district area engaged in food processing business, most of them have not been able to make simple financial statements. To facilitate the recording of business transactions, the service team will introduce a Smartphone-based SME Application. Most business actors still lack understanding of SME applications and cannot use them. The purpose of the service activities carried out by the Lecturer Team of the Faculty of Economics, University of Semarang is to introduce Smartphone-based SME Applications and socialize the features of SME Applications and how to use them. The service activity will be held on Friday, November 10, 2023. The implementation of service activities at Balai RW 07 Building Jl. Serayu I, Bugangan Village, East Semarang District.The activity was carried out for one day from 13.00 to 15.00 (1 x 2 hours). Service activities are carried out using lectures, training and discussion/question and answer methods. The work procedure for service activities is carried out through several stages, including the identification stage, preparation stage, implementation stage, monitoring and evaluation stage, reporting and publication stage. The material presented was to introduce the features of the SME Application and how to use it. SME Application features consist of journals, general ledgers, balance sheets, profit and loss, balance sheets, periods, debts, receivables, excel exports and income tax returns. Keywords: Sme Application, Smartphone-Based, Financial Report